Survival Outcomes by High-Risk HPV Status in Non-Oropharynx Head and Neck Squamous Cell Carcinomas: A Propensity-Scored Analysis of the National Cancer Data Base - Tian, Sibo (Cancer, 2019)
BACKGROUND: The prognostic relevance of human papillomavirus (HPV) status in non-oropharyngeal (OPX) squamous cell cancer (SCC) of the head and neck is controversial. We evaluated the impact of high-risk HPV status on overall survival (OS) in patients with non-OPX SCC using a large database approach. METHODS: The National Cancer Data Base was queried to identify patients diagnosed from 2004–2014 with SCC of the OPX, hypopharynx (HPX), larynx, and oral cavity (OC) with known HPV status. Survival was estimated using Kaplan-Meier methods; distributions were compared with log-rank tests. Propensity score matching (PSM) and inverse probability of treatment weighing (IPTW) methods were utilized; cohorts were matched on age, sex, Charlson-Deyo score, clinical group stage, treatments received, and anatomic subsite. Propensity analyses were stratified by group stage. RESULTS: 24,740 patients diagnosed from 2010–2013 were analyzed; 1,085 patients with HPX, 4804 with larynx, 4,018 with OC, and 14,833 with OPX SCC. The proportions of HPV positive cases by site were: 17.7% in HPX, 11% in larynx, 10.6% in OC, and 62.9% in OPX. HPV status was prognostic in multiple un-adjusted and propensity-adjusted non-OPX populations. HPV positivity was associated with superior OS in HPX SCC with hazard ratio (HR) of 0.61 (p<0.001, IPTW), in stage III-IVB laryngeal SCC (HR 0.79, p=0.019, IPTW), and in stage III-IVB OC SCC (HR 0.78, p=0.03, IPTW). CONCLUSIONS: Positive high-risk HPV status is associated with longer OS in multiple non-oropharynx head and neck populations – hypopharynx, locally-advanced larynx and oral cavity. If prospectively validated, these findings have implications for risk-stratification.